Ghosts of our Lives: a Hauntological Reading of Multiverse Fiction in Contemporary Verbo-Visual Media - Busi Rizzi, Giorgio; Di Paola, Lorenzo (Cinergie – Il Cinema e le altre Arti, 2025)
This article explores the multiverse as a recurring narrative and symbolic configuration in contemporary verbo-visual media. It interprets it as the articulation of a hauntological condition, shaped by the erosion of ontological certainties regarding the present and the past, along with the collapse of future possibilities. Tracing the concept’s trajectory from philosophical speculation and theoretical physics to a comparative analysis of comics, television, and contemporary cinema, the article asserts that multiverse fiction serves as both a consequence and a narrative response to the crisis of temporality, identity, and futurability in late capitalism. Drawing on the idea of hauntology, we investigate how multiverse fiction has transformed from a speculative trope into a complex framework for navigating cultural anxieties associated with the instability of truth, media fragmentation, and ecological crisis. The article asserts that multiverse fiction facilitates narrative negotiations of unrealised presents and foreclosed futures, serving both as a product and a critique of post-postmodern temporal dislocation. Rather than providing resolution, it thus functions as a compromise formation mediating between escapism and critical engagement, creating speculative spaces for mourning, reimagining, and symbolically rehearsing alternative realities.